The effects of pair-programming in introductory programming courses with visual and text-based languages - Korber, Patrick; Motschnig, Renate (Proceedings - Frontiers in Education Conference, 2021)
This full research to practice paper investigates the setting of pair-programming focusing on its effects on students' learning to program when using a visual versus text-based programming language. In particular, we are interested whether there are any differences in learning outcomes and social/motivational factors to keep in mind when learners' make their initial steps in programming in a visual versus text-based language while employing a pair-programming approach. First a systematic literature review (SLR) was conducted, encompassing searches in the ACM Digital Library, IEEE Xplore/Electronic Library, LNCS (Springer), and Google Scholar. The results of the SLR informed the second step, namely the design of a qualitative study consisting of the evaluation of students' achievements, a questionnaire, and focus interviews with students at secondary level (K10). Students worked in pair-programming (PP) and solo-programming (SP) mode while using a visual language (MIT App Inventor) and a text-based language (Python), respectively. In a nutshell, we found that regarding achievement, students tended to earn more points in the PP setting. This tendency was more distinct in the text-based condition compared to visual programming. In both conditions, students responded that in the PP setting they had more fun solving the assignments and the PP setting had helped to solve problems faster. Aside of the scientific findings, the paper describes the didactic concepts used in order to inspire educators to engage in similar practice and research. With this contribution we aim to enrich educators' and researchers' repertoire of making introductory programming lessons more engaging and successful.